EFEKTIVITAS KOMUNIKASI LINGKAR KEBUN PTPN III, KEBUN SEI PUTIH (STMIK Dharmapala Riau, 2021)
The effectiveness of communication in the plantation can be seen from the circumference of the garden in the form of internal and external problems. Effectiveness is the goal of the ability to utilize human resources something appropriately, clear and universally acceptable standards, Employee Performance Gardens and Garden Circles is a routine how to use a little time can explain the work. This problem can have an impact on socio-cultural aspects to refer to performance problems. The ability of approach and motivation must be able to be carried out by an assistant, both the ability of dialogue, humility, trust, hope and critical thinking, in order to provide harmony for plantation companies.